Evaluating LINE-1 methylation in cleft lip tissues and its association with early pregnancy exposures. (January 2018) - Khan, Mohammad Faisal J; Little, Julian; Mossey, Peter A; Steegers-Theunissen, Régine PM; Autelitano, Luca; Lombardo, Ilenia; Andreasi, Rita Bassi; Rubini, Michele
Aim: To pilot investigation of methylation of long interspersed nucleotide element-1 in lip tissues from infants with nonsyndromic cleft lip, and its association with maternal periconceptional exposures.Methods: The lateral and medial sides of the cleft lips of 23 affected infants were analyzed for long interspersed nucleotide element-1 methylation by bisulfite conversion and pyrosequencing.Results: The medial side showed 1.8% higher methylation compared with the lateral side; p = 0.031, particularly in male infants (2.7% difference; p = 0.011) or when the mothers did not take folic acid during periconceptional period (2.4% difference; p = 0.011). These results were not statistically significant when Bonferroni adjustment was used.Conclusion: The observed differences in DNA methylation, although nonsignificant after correction for multiple comparisons, suggest that differential regulation of the two sides may impact lip fusion and warrant larger-scale replication.